2018
DOI: 10.1097/meg.0000000000001156
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells for hepatitis B virus-related acute-on-chronic liver failure: a systematic review with meta-analysis

Abstract: Our pooled results suggested that MSC treatment could significantly reduce the mortality rate, without increasing the incidence of severe complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Despite rash and fever (37-38 • C) in several cases that resolved without additional treatment (24), no significant adverse effects were reported in most clinical trials. A series of meta-analysis results also proved the therapeutic efficacy and safety of MSCs from different sources in patients with ALF, liver cirrhosis and end-stage liver disease associated with HBV and HCV (22,(140)(141)(142).…”
Section: Safety Issues Associated With Msc Transplantationmentioning
confidence: 87%
“…Despite rash and fever (37-38 • C) in several cases that resolved without additional treatment (24), no significant adverse effects were reported in most clinical trials. A series of meta-analysis results also proved the therapeutic efficacy and safety of MSCs from different sources in patients with ALF, liver cirrhosis and end-stage liver disease associated with HBV and HCV (22,(140)(141)(142).…”
Section: Safety Issues Associated With Msc Transplantationmentioning
confidence: 87%
“…Another study on MSC transplantation for the treatment of ACLF patients also achieved similar results, in which the treatment increased the 24-wk survival rate, improved liver function, and decreased the incidence of severe infections[11]. Moreover, we recently conducted a systematic review and meta-analysis of MSC transplantation in ACLF patients, which showed that the treatment significantly reduced mortality rates, without increasing the incidence of severe complications[13]. There were also no differences in the incidence of severe complications ( e.g ., encephalopathy, hepatorenal syndrome, gastrointestinal bleeding) between the standard medical treatment and the MSC treatment group in ACLF patients[5].…”
Section: Treatment Of End-stage Liver Disease Via Stem Cell Transplanmentioning
confidence: 79%
“…In the era of regenerative medicine, MSCs have emerged as a novel approach for HBV-ACLF treatment due to their ability to home to damaged tissues, hypoimmunogenicity that allows allogenic transplantation, anti-inflammatory effects and their differentiation capacity into functional hepatocyte-like cells [36,37]. An study by Peng and colleagues investigated the therapeutic effects of single transfusion of culture expanded autologous Bone marrow (BM)-MSCs in HBV-associated liver failure patients [38].…”
Section: Mscs and Hepatitis B Virus (Hbv)mentioning
confidence: 99%